Serum CRP, MDA, Vitamin C, and Trace Elements in Bangladeshi Patients with Rheumatoid Arthritis - Das, Dalim Chandra; Jahan, Israt; Uddin, Md. Giash; Hossain, Md. Monir; Chowdhury, Muhammed Alamgir Zaman; Fardous, Zeenath; Rahman, Md. Mujibur; Kabir, A. K. M. Humayun; Deb, Sudip Ranjan; Siddique, Md. Abu Bakar; Das, Abhijit (Biological trace element research, 2021)
Rheumatoid arthritis (RA) is an autoimmune disorder that is a painful health crisis. This study aimed to assess the serum C-reactive protein (CRP), malondialdehyde (MDA), non-enzymatic antioxidant (vitamin C), and trace elements (Zn, Cu, Mn, and Fe) in RA patients, and thereby correlate these parameters with the association of RA. This study included 20 Bangladeshi RA patients and 20 normal healthy volunteers as control subjects. CRP level was determined using a laboratory-based latex agglutination–enhanced immunoassay. The lipid peroxidation level was determined by measurement of the serum level of MDA. Non-enzymatic antioxidant vitamin C was assessed by UV spectrophotometric method. Trace elements were determined by atomic absorption spectroscopy (AAS). Our study observed significantly higher concentrations of CRP ( p < 0.001) and MDA ( p < 0.001), and significantly lower concentrations of vitamin C ( p < 0.001) in the RA patient. The mean values of Zn, Cu, Mn, and Fe were 6.62 ± 0.34, 1.42 ± 0.17, 7.51 ± 0.23, and 29.25 ± 0.41 ppm for the RA patients respectively and 13.57 ± 9.13, 1.15 ± 0.17, 1.59 ± 0.18, and 62.47 ± 5.25 ppm for the control subjects, consequently. There was a significant difference ( p < 0.05) in the trace element levels between the RA patients and control subjects. Our study suggests that a higher concentration of CRP and MDA, lower levels of vitamin C, and altered trace elements may be linked to RA.